Paraguay : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2006)
The country lacks an integrated statistical framework that would take account of the various analytical and accounting linkages across macroeconomic statistics, and the relationships between regulatory tools, intermediate objectives, and policy goals. There is significant room to improve the methodological soundness, accuracy, and reliability of the statistics, for instance, by expanding the data sources for most sectors, as well as by strengthening data validation and statistical techniques for most datasets. Paraguay should improve the access to official statistics and metadata.